Elevated metabolic score for visceral fat was associated with increased prevalence of gallstones in American adults: a cross-sectional study - Lin, Hao; Shi, Kexuan; Luo, Shuang; Ye, Wu; Cai, Xiaoniao (Frontiers in Medicine, 2024)
Background Metabolic Visceral Fat Score (METS-VF) recently introduced is posited to be a superior metric for assessing visceral adipose tissues (VAT) compared to traditional obesity indexes. This study aims to elucidate the correlation between METS-VF and the incidence of gallstones. Methods In this cross-sectional study, the data from the National Health and Nutrition Examination Survey (NHANES) during the period from 2013 to 2020 were analyzed. And the correlation between METS-VF and the incidence of gallstones was explored through multivariate logistic regression analysis, receiver operating characteristic (ROC) curve, subgroup analysis and restricted cubic spline (RCS) regression. Results This study included 5,975 participants, of whom 645 (10.8%) were gallstone formers. As the quartile range of METS-VF increased, a notable rise in the prevalence of gallstones was observed (3.2% vs. 7.4% vs. 12.1% vs. 20.6%, p < 0.001). Logistic regression analyses indicated a significant positive correlation between METS-VF and the risk of gallstones (OR = 3.075, 95% CI: 2.158, 4.381). Subgroup analyses further revealed a stronger correlation between gallstones and METS-VF in subjects over 50 years old. RCS regression identified a non-linear positive correlation, with an inflection point at 6.698. Finally, the area under the ROC curve (AUC) of METS-VF was significantly larger (AUC = 0.705, 95%: 0.685, 0.725) than those of traditional obesity indexes and other VAT surrogate markers. Conclusion This study is the first to reveal a significant positive correlation between the prevalence of gallstones and METS-VF, with METS-VF outperforming other VAT surrogate markers in the diagnosis of gallstones.